Islamic Educational Values, Teacher Feedback, and Academic Resilience as Predictors of Self-Regulated Learning among Madrasah Students - Rifqoh, Fany; Muhammad Nur Wangid; Suwarjo; Yulia Ayriza (International Journal of Islamic Educational Psychology, 2026)
Research on self-regulated learning (SRL) in Islamic secondary education has predominantly emphasized pedagogical and psychological factors, while the role of Islamic educational values as a contextual determinant remains underexplored. This study addresses this gap by examining the structural relationships between Islamic Educational Values, Teacher Feedback, Academic Resilience, and Self-Regulated Learning among Madrasah Tsanawiyah students, with a focus on integrating moral, instructional, and psychological dimensions. A quantitative cross-sectional design was employed, involving 200 Madrasah Tsanawiyah students, and the data were analyzed using SEM-PLS. The results showed that Islamic Educational Values (t = 4.612, p < .001), Teacher Feedback (t = 2.487, p = .014), and Academic Resilience (t = 3.105, p = .002) were positively associated with Self-Regulated Learning. The model explained 56.2% of the variance in Self-Regulated Learning (R² = 0.562) and demonstrated satisfactory predictive relevance (Q² = 0.503). These findings provide empirical evidence that Islamic Educational Values, alongside Teacher Feedback and Academic Resilience, significantly contribute to students’ self-regulated learning. The study’s novelty lies in empirically examining an integrated SEM-PLS model that combines moral, pedagogical, and psychological constructs within the context of Islamic secondary education.